SEJARAH PERKEMBANGAN HISAB DAN RUKYAT - hidayat, Ehsan Hidayat (UIN ALAUDDIN MAKASSAR, 2019)
Hisab and rukyat are two methods used in the determination of the Muslim worship time, such as Ramadan fast, five times prayer, Eid al-Adha sacrifice, and also for the benefit of human in general. observation of the sky made by humans is an activity that is closely related to the needs of man himself. History summarizes the journey of Falak science treasures in the early determination of the kamariyah months from the discovery of classical methods to development in the modern era. The initial method used was the role of both eyes as the human optic of the moment to see the moon on the 29th of the lunar month. And as the times progressed to the method of rukyatul hilal by combining the modern product of the telescope. The position of reckoning that one side of the rukyah can not be separated in its development. Known at the time of the dinas umayah development of astronomy began to be shaken, that is with the translation of the prime work of books of astronomy from Greek to Arabic. Miftah an-nujum that is adopted into hermes is the first Muslim heart book. And to the works of the modern era that colored many of rukyat itself.Keyword : Hisab and rukyat, the beginning of the month kamariyah, history